The secret of the snake - Rose, Stephen; Vaughn, Paul; Ronowicz, Stefan (London : BBC Enterprises, 1982)
The film explores the reasons for man's aversion to these retiles, the biological nature of his fears and the extent to which rational explanation can overcome them. The film also takes a fascinating close-up look at the behaviour of the snakes at their natural habitat
Backup available in VHS 1/2 in.
Keywords: Snakes; Snakes -- Behavior; Poisonous snakes -- Venom